A Lie group treatment on a generalized evolution Fisher type equation with variable coefficients - Yao, Shao-Wen; Hashemi, Mir Sajjad; İnç, Mustafa (Elsevier, 2023)
In this study, a general second-order evolution equation of the Fisher-type, with time-dependent variable coefficients, is considered. This equation contains many well-known equations, and obtained results may be applicable in investigating other evolution equations. Lie symmetries and corresponding invariant solutions of the considered problem are studied by a non-traditional Lie symmetry method (LSM). Prolongation of the model is an essential part of the Lie symmetry method, which in the current work, we analyze by the heir-equations. Finally, different types of solutions depending on the variable coefficients, such as the exponential solutions, trigonometric solutions, Bessel solutions, and Mathieu solutions, are extracted.
Keywords: Heir-equation method; Non-classical symmetry; Fisher-type equation